2022
DOI: 10.1038/s41467-022-33315-8
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the human insulin receptor by non-insulin-related peptides

Abstract: The human insulin receptor signalling system plays a critical role in glucose homeostasis. Insulin binding brings about extensive conformational change in the receptor extracellular region that in turn effects trans-activation of the intracellular tyrosine kinase domains and downstream signalling. Of particular therapeutic interest is whether insulin receptor signalling can be replicated by molecules other than insulin. Here, we present single-particle cryoEM structures that show how a 33-mer polypeptide unrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…These results are consistent with the previously proposed hypothesis that the site 1 binding peptide marks the hotspot involved in insulin-induced activation of the insulin receptor, whereas the site 2 binding peptide may be more related to affinity and can act as an antagonist in IR phosphorylation . Moreover, recent structural works revealed that the site 1 peptide shared the same binding space as native insulin suggesting a redundant role of the site 1 peptide. While in the case of Ins-AC-S2-mut5, it exhibited a similar potency (i.e., EC 50 of 3.2 nM) and maximal activity to that of native insulin. This result confirmed the full agonistic activity of Ins-AC-S2-mut5 relative to native insulin and the S2 hotspot (i.e., “SLEEE”) in triggering antagonistic activity.…”
Section: Resultssupporting
confidence: 89%
“…These results are consistent with the previously proposed hypothesis that the site 1 binding peptide marks the hotspot involved in insulin-induced activation of the insulin receptor, whereas the site 2 binding peptide may be more related to affinity and can act as an antagonist in IR phosphorylation . Moreover, recent structural works revealed that the site 1 peptide shared the same binding space as native insulin suggesting a redundant role of the site 1 peptide. While in the case of Ins-AC-S2-mut5, it exhibited a similar potency (i.e., EC 50 of 3.2 nM) and maximal activity to that of native insulin. This result confirmed the full agonistic activity of Ins-AC-S2-mut5 relative to native insulin and the S2 hotspot (i.e., “SLEEE”) in triggering antagonistic activity.…”
Section: Resultssupporting
confidence: 89%
“…However, binding to Site 2 alone is apparently not sufficient to trigger a structural change in the IR that could lead to its activation, possibly due to its inability to reduce the known conformational flexibility of the apo‐IR 3,39 . This hypothesis is supported by unsuccessful attempts to obtain the cryo‐EM structure of IR in complex only with IM172N22 by Kirk et al 23 and by the inactive apo‐like IR structure bound to S597N22 peptide by Park et al 24 On the other hand, the complex of IR with simultaneously bound mimetic peptide in Site 2 and insulin in Site 1 23 shows that binding of the mimetic peptide to Site 2 is unlikely to completely prevent insulin binding to Site 1, and this could be the mechanism of the only partial antagonism of S592 and its derivatives in the presence of insulin, where even at the highest peptide concentrations, the receptor is still active at approximately 30% of its maximal activity. It is also possible that the different chemical staples in our cyclic peptides may not only affect the binding of the peptide to Site 2 but may also interfere differently with the binding of insulin to vacant Site 1, for example, by imposing less or more structural constraints on the insulin molecule, which may result in their disproportionate binding‐activating properties.…”
Section: Resultsmentioning
confidence: 99%
“…Mouse embryonic fibroblasts (IR-A) derived from IGF-1R knockout mice and stably transfected with human IR-A, kindly provided by A. Belfiore (Catanzaro, Italy) and R. Baserga (Philadelphia, Pennsylvania, USA), were grown as described previously. 25 Ligand-dose response IR-A autophosphorylation levels for the analogs were determined using an in-cell Western assay adapted for chemiluminiscence as described in Machackova et al 28 Briefly, the IR-A cells were plated at 20,000 cells/well in white 96-well Brand plates cell grade (Brand GMBH, Germany) and incubated for 24 h. The cells were starved for Anti-actin (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) antibody (Sigma-Aldrich, cat. A5060) was used as a loading control.…”
Section: Receptor Phosphorylation Assay and Antagonism Assaymentioning
confidence: 99%
“…Two binding sites equivalent to insulin's sites 1 and 2 have also been identified on IGF-I and II by site-directed mutagenesis (Gauguin et al, 2008;Alvino et al, 2009), with site 1 extending into their C-domain. The engagement of insulin/IGFs site 1 and 2 in hIR/mIR/IGF-1R binding was ultimately confirmed in the last decade in over 40 crystal and cryoEM structures of complexes of these hormones (as well as insulin mimetic peptides and aptamers) with their cognate receptors and their extensive functional studies ( Kavran et al, 2014, Croll et al, 2016Weis et al, 2018;Xu et al, 2018Xu et al, , 2020Xu et al, , 2022Scapin et al, 2018;Gutmann et al, 2018Gutmann et al, , 2020Uchikawa et al, 2019;Li et al, 2019Li et al, , 2022Blyth et al, 2020;Zhang et al, 2020Xiong et al, 2022;Nielsen et al, 2022;Wu et al, 2022;Kirk et al, 2022;Park et al, 2022;Kim et al, 2022; for reviews, see Lawrence, 2021;Forbes, 2023).…”
Section: Introductionmentioning
confidence: 94%
“…The copyright holder for this this version posted February 17, 2023. ; https://doi.org/10.1101/2023.02.17.528932 doi: bioRxiv preprint Kirk et al, 2022;Park et al, 2022;Kim et al, 2022; for reviews, see Lawrence, 2021;Forbes, 2023).…”
Section: Introductionmentioning
confidence: 99%